2016
DOI: 10.1167/iovs.16-19955
|View full text |Cite
|
Sign up to set email alerts
|

Optical Detection of Early Damage in Retinal Ganglion Cells in a Mouse Model of Partial Optic Nerve Crush Injury

Abstract: PurposeElastic light backscattering spectroscopy (ELBS) has exquisite sensitivity to the ultrastructural properties of tissue and thus has been applied to detect various diseases associated with ultrastructural alterations in their early stages. This study aims to test whether ELBS can detect early damage in retinal ganglion cells (RGCs).MethodsWe used a mouse model of partial optic nerve crush (pONC) to induce rapid RGC death. We confirmed RGC loss by axon counting and characterized the changes in retinal mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Many studies have monitored RGC axon bundle health in primates, 20 , 21 rodents, 22 24 and human patients. 25 27 In isolated rat retinas, optical properties, such as the RNFL reflectance spectrum and birefringence, were found to be different following chronic ocular hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have monitored RGC axon bundle health in primates, 20 , 21 rodents, 22 24 and human patients. 25 27 In isolated rat retinas, optical properties, such as the RNFL reflectance spectrum and birefringence, were found to be different following chronic ocular hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…One discrepancy between our study and the previous study is that ex vivo retinas have VN ratio larger than 1 while we found VN ratio slightly less than 1 from in vivo retinas when we compared visible and NIR bands centered at 560 and 820 nm. The study by Yi et al 54 used fixed ex vivo retinas and only investigated changes in visible light range by confocal reflectance microscopy. The study by Huang et al 24 used different device and normalization methods for spectral characterization and used a different ex vivo preparation for retina culturing.…”
Section: Discussionmentioning
confidence: 99%
“…Vis-OCT will be likely to bring more benefit in clinical diagnosis and management of glaucoma since it has demonstrated higher contrast and higher resolution in imaging RNFL 22 , 40 . In addition, before changes in retinal layer thickness can be observed, subdiffraction cellular damages were found to be encoded in the scattering spectrum within the visible spectral range, 45 , 91 , 92 which can potentially be detected by vis-OCT. AMD is another leading cause of blindness whose early diagnosis draws attention from both researchers and clinical practitioners. Aging of the RPE and loss of the RPE melanin play important roles in pathogenesis of AMD.…”
Section: Perspective Of Vis-octmentioning
confidence: 99%
“…Investigations of vis-OCT have moved from phantom demonstration 34 36 to in vivo verification, 25 , 37 from animal experiments 38 , 39 to clinical studies, 22 , 40 , 41 and from technical development 21 , 42 , 43 to pathological investigations of several diseases 44 47 Until now, vis-OCT has been applied to imaging different anatomical sites, including the retina, 48 , 49 brain cortex, 50 53 and female reproductive tract (FRT) 23 , 54 . Multimodal systems combining vis-OCT with other imaging platforms have been developed to reveal comprehensive information in the examined tissue 40 , 52 , 55 …”
Section: Introductionmentioning
confidence: 99%